Effects of heterogeneous risk factors on psychological distress in adolescents with autism and victimization experiences in Taiwan. Issue 1 (2nd January 2018) - Chiu, Yu-Lung; Kao, Senyeong; Tou, Shao-Wen; Lin, Fu-Gong
Abstract: Purpose: To investigate the prevalence of various types of bullying victimization among adolescents with autism spectrum disorder (ASD) and examine the effects of victimization on the mental health of adolescents with ASD. Methods: The sample was collected from the Special Needs Education Longitudinal Study (SNELS) database released in 2011. Variables comprising seven psychological distress (PD) items and four types of bullying victimization and family-, school-, and peer-related factors were included in a multivariate regression analysis. Results: Exclusion and verbal bullying were most frequently reported, 72.4% of students with ASD experiencing exclusion bullying and 66% of them experiencing verbal bullying. Among the victims, delayed bedtime, use of medication, and conflicts with parents significantly increased PD. By contrast, good relationships with parents and friends and liking school environments relieved PD symptoms. Furthermore, delayed bedtime after 12 a.m. enhanced the effects of exclusion victimization on PD in the participants. Conclusions: Our results indicated that bullying victimization among adolescents with ASD was a risk factor for their psychological well-being. Nevertheless, good parent–adolescent and interpeer relationships improved their mental health. Our results can serve as a reference in implementing strategies for motivating parents and teachers to pay more attention to the needs of adolescents with ASD. Implications for Rehabilitation: More than 80% of adolescents with autism experience at least one type of bullying victimization. Bullying victimization attributes to a major factor influencing mental health of adolescents with autism. Good parent–adolescent and interpeer relationships can play beneficial roles in improving mental health of the adolescents.